From mother tongue to English: Exploring the transition and student investment in an English medium university : A case study from Sri Lanka - Kalinga, Jayathri (My University, 2025)
The study was stimulated by the low English proficiency of Sri Lankan school students in national exams, the requirement to shift to English Medium Instruction (EMI) in university, and the lack of literature on EMI in non-state universities and STEM fields in Sri Lanka. This study explored the transition from mother-tongue instruction to English medium instruction and the student investment in L2 practices through the lens of Darvin and Norton’s Model of Investment. Three research questions of the study reflect identity, capital, and ideology: the three components of the framework. The research questions of the study are: How do students negotiate and (re)construct their linguistic and academic identities as they transfer from mother-tongue instruction to English medium instruction? How do students utilize their existing capital and acquire new capital during their adaptation to English medium instruction? How do language and societal ideologies shape the students’ investment in English medium studies? A single embedded case study method is used as the research design as the study focuses on a particular non-state university in Sri Lanka. The population of the study comprises all non-state university students in Sri Lanka, while the sample includes students from the Faculty of Science in a selected non-state university. The sample size was seven. Empirical data was obtained through a demographic data form, one-on-one semi-structured interviews, and a drawing of an identity portrait. Interview data was analyzed using thematic analysis, while the identity portraits were analyzed using content analysis. The findings revealed three main themes, identity, capital, and ideology, which align with the theoretical framework. Despite being proud of their ethnic, religious, and cultural identity, the participants acknowledged the importance of English proficiency and EMI studies for their future. The findings also revealed that the participants are becoming legitimate speakers of English to a certain extent, although it is affected by their multilingual identity and the use of L1. The majority of the participants portrayed a high-performing and motivated English learner identity during their school education, and it was challenged at the university as some reverted to underperforming learners due to their English proficiency. In addition, the imagined-self identity of the learners mediated the high-performing and motivated English learner identities. It has been noticed that the participants' investment in learning English depends on the financial status of the family, the presence of different ethnic groups at the school, university, and residential area, and the support received and not received from the teachers, family members, and friends. Moreover, the participants' existing English knowledge, subject-specific English vocabulary, English speaking skills, and opportunities available to use English determine the level of capital for L2 practices. In addition, the findings revealed that the participant's investment in L2 practices is shaped by their nationalist, globalization, and neoliberal ideologies as well as the English as a class marker ideology. The main implications of the study are evaluating the existing university English modules, providing general English, EAP, and ESP modules to ease the transition to EMI, and revisiting the national curriculum and educational policy of the country to suit the needs of the current society and to minimize the issues faced due to MoI transition.
Keywords: English medium instruction, transition, identity, capital, ideology